Moolaadé (<<Les>> Films du Paradoxe, 2007)
It is the time for the young girls of a village to be "purified" by ritual circumcision. The women know that many girls die after the operation, but the men of the village insist on the ceremony. Since the village men will not marry an un-cut woman, the older women insist on the ritual, too, as their daughters must find husbands. Colle has kept her daughter from being circumcised, and several of the girls go to her for refuge. Colle agrees to help them, and she invokes "moolaade," a form of sanctuary.